Experiential Learning of New International Financial Reporting Standards: Case-based Learning of IFRS 10 and IFRS 11 - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2013)
Do you have problems getting your students to read the accounting standards? Are you always running out of class time because the standards just get more complicated? Are you frustrated with the lack of curriculum resources that are lagging behind the new accounting standards? Do you often agonize over whether to teach an existing or a future standard that isn’t effective yet? Increasingly, the IASB and FASB issue new standards that won’t be effective until two or three years later, and in that time period, they may change yet again! This presentation proposes that carefully designed project assignments may help the overwhelmed professor to deal with the resource crunch. However, more importantly, these assignments are geared towards the development of life-long habits in students to read and deconstruct new standards in an increasingly dynamic and complex accounting environment.